Design of STEM-based teaching materials for basketball - Sari, Oktaria Novia Kurnia; Bayu, Wahyu Indra; Ramadhan, Arizky; Iyakrus, Iyakrus; Usra, Meirizal; Yusfi, Herri (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2024)
This study aims to apply STEM-based teaching materials to learn Physical Education in Junior High School basketball material. This study uses a development research approach, the ADDIE model. The results showed that STEM-based teaching materials in junior high school basketball materials have been assessed as feasible to apply to students based on expert assessment. In the first validity test, the score obtained was 90%, with a very feasible category with some improvements. In the second validity test, the product scored 93% with a very feasible category without improvement, and in the third validity test, the score obtained was 97% with a very feasible category. At the implementation stage, STEM-based teaching materials proved effective when applied to basketball learning. This can be seen from the increase in the average value of student learning outcomes, with a pretest value of 72.52 which increased to 78.17 on the post-test, with a tcount of 8.982> ttable 1.675 at α = 0.05. So, it can be concluded that STEM-based teaching materials on basketball material at the Junior High School level are valid, applicable, effective, and feasible to use.